Optimum Energy Flow from Source in Transient State - Konrad Hawron; Bartosz Rozegnał; Maciej Sułowicz (Energies)
This article presents an extended algorithm for one of the most important tasks in source–receiver optimal cooperation—minimization of the source’s RMS current value while ensuring the required active power is supplied to the receiver. The current state of the art ensures optimal steady-state cooperation. The presented extension introduces an approximated transient state to the optimization equations. By using an extended algorithm, it is possible to provide the optimal current not only in a steady state but also at any time during the transient state. The influence of the assumed transients—finite and permanent—on the EMF and optimal current signals is shown. The obtained results are compared with conventional calculation methods to show the advantage of the presented algorithm. The developed algorithm was also tested on measurement data obtained from a real-world test setup that reflects an actual section of the power system. The article also demonstrates, using a measurement example, how the proposed current optimization process during fault conditions in the power system can contribute to reducing short circuit-related losses.